Hydrochemical evolution of pore water in riverbed sedimentation zone during riverbank infiltration - Shuai Lu (IWA Publishing, 2021)
The riverbed sedimentation zone is an important zone of hydrochemistry, and the biogeochemical action in this zone has a significant impact on groundwater quality. As the main area where hydrochemistry occurs, studying the law of hydrochemical evolution within 1 m below the riverbed is of great significance for understanding the migration and removal of river pollutants. In this study, a combination of onsite monitoring and indoor experiments was used to analyze the variation characteristics of the hydrochemical composition of pore water during riverbank infiltration, as well as the main hydrochemical effects and influencing factors. The results show that in the process of river water infiltration, a series of redox reactions occur in the riverbed sedimentation zone, and there are differences in different infiltration depths. From 0 to 20 cm below the riverbed, strong respiration and denitrification mainly occurred. Reductive dissolution of manganese minerals mainly occurred from 20 to 60 cm, and reductive dissolution of iron minerals mainly occurred from 60 to 90 cm. River water level, dissolved organic carbon content and microbial activity had varying degrees of influence on these redox effects. The recharge of river water infiltration ensures the exploitation amount of the pumping wells, but it also leads to the increase of some components in groundwater, and the extracted water cannot be directly drunk. HIGHLIGHTS The main control effect of hydrochemical evolution in the riverbed sedimentation zone is redox, and there are differences in different infiltration depths.; The redox effects were affected by river water level, dissolved organic carbon content and microbial activity.; The recharge of river water infiltration ensures the exploitation amount of the pumping wells, but it also leads to the increase of some components in groundwater.;